Low-fee Private Schooling: Poor Households' Struggle to Support Their Children's School Attendance in Unauthorized Colonies in Delhi, India. Issue 2 (2nd April 2020) - Mousumi, Manjuma Akhtar; Kusakabe, Tatsuya
ABSTRACT: The growth of private schools in India has contributed significantly to increased student enrollment but also raises certain questions, such as how parents living in informal settlements can support their children's school attendance and seek alternative options, such as private schools, for their children. This paper addresses these under-researched aspects by focusing on the concerns of Muslim parents (who have a minority status in India) living in unauthorized colonies in relation to selecting a school. The data were generated through questionnaires and semi-structured interviews. Drawing upon data from 13 principals and 35 households in unauthorized colonies in Delhi, India, the key findings suggest that parents face difficult conundrums due to geographic and social background constraints. Issues regarding the selection of private schools and the challenges of finding schools are discussed. This study provides a different context that should be used to inform policymakers and educators examining schooling options for marginalized communities/parents in illegal settlements.